A LATE-PRESENTING ESOPHAGEAL PERFORATION COMPLICATED BY ESOPHAGOMEDIASTINAL FISTULA (Vietnam Journal of Community Medicine, 2026)
Background: Esophageal perforation is a possibly life-threatening condition with mortality ranging from 10-40%. Delayed diagnosis, especially from fish bone ingestion, increases the risk of mediastinitis and chronic esophagomediastinal fistula.Case presentation: A 28-year-old male experienced retrosternal pain after suspected fish bone ingestion and self-medicated without investigation. Symptoms subsided initially, but he developed chronic cough for 5 months after ingestion. Chest CT revealed a chronic esophagomediastinal fistula. The patient was treated with esophageal stenting. At 8 weeks follow-up, endoscopy confirmed complete healing of the fistula and the migrated stent-found in the stomach-was safely removed.Conclusion: Delayed presentation of esophageal perforation may have an insidious course and is easily overlooked. Persistent respiratory symptoms in patients with a history of foreign body ingestion warrant imaging evaluation to rule out chronic fistula. Esophageal stent placement is an effective treatment option.
Keywords: Esophageal perforation, fish bone, stent, mediastinal fistula, delayed diagnosis.